The Detox Diet - Shonali Sabherwal (Ebury Press/ Penguin Books, 2017)
Shonali Sabherwal is a celebrity nutritionist who specializes in improving immunity, removing toxins, managing weight, reversing leaky-gut syndrome and other autoimmune ailments by first altering the biodiversity of the gut. In her new book The Detox Diet, she sheds light on how the root of everything connected to our health lies in the inner ecosystem. She helps unravel the secrets of weight loss, anti-ageing, beauty and autoimmune diseases, and teaches us how to reverse the health issues she believes arises when bad bacteria outdo the good ones in our system, causing an imbalance. With three fantastic detox diet plans, numerous recipes and an abundance of health tips, this book will help you finally understand the reasons behind many of the problems for which you earlier had no answers. It will now not only get you into the best shape you have ever been in but also help you maintain and sustain a healthier lifestyle.
Keywords: Nutrition